Handbook of electric motors - Toliyat, Hamid A.; Kliman, G.B (Electrical and computer engineering, 1995)
This handbook provides comprehensive coverage of every type of electric motor in use today, from the generic forms of direct current induction, and synchronous machines, to permanent magnet DC motors, linear induction motors and stepper motors. Related topics such as finite element analysis, control, protection, testing, reliability, maintenance, specification procedures, and environmental and mechanical factors are discussed.